PERAN KEPEMIMPINAN DAN KEBIJAKAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MAN 1 YOGYAKARTA - Abd Adam Salam (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
Leadership is an important issue for a group or institutional organization. This is because the leader is one of the factors that greatly influences the success of the group in achieving its goals. This study aims to describe the role of leadership and madrasa head policies in improving the quality of education. This study uses the method of observation, interviews, and documentation then uses descriptive qualitative analysis. The results of this study are: first, the Head of MAN 1 Yogyakarta as a leader performs his role by establishing the vision and mission of madrasas in 1 Yogyakarta, setting the objectives of madrasa education in 1 Yogyakarta, acting as a motivator, acting as a supervisior. Second, seen from the achievements achieved MAN 1 Yogyakarta there are various qualities achieved such as quality in the fields of research, tahfidz (memorization of the Qur'an), religion, organization, further study programs abroad. Third, improving the quality of education for Madrasah principals is inseparable from three supporting factors such as: loyalty, commitment and integrity.